Efeito da adição de cloreto de alumínio a soluções tamponadas de acetato de sódio sobre a solubilização da apatita de Araxá - Rabelo Junqueira, Rosa Maria; Ribeiro, Antônio Carlos (Revista Ceres, 2025)
The solubility of a phosphate rock from Araxd, Minas Gerais, Brazil was studied in sodium acetate buffer solution at pH 3.0 and 4.0. Different aluminum levels (0.0., 0.5., 1.0., 2.0., 4.0. and 8.0 mg Al3+) were added in 20 ml solution and the rock solubilization was measured as calcium and phosphorus recovery. The rock solubilization was greater at pH 3.0 than at 4.0. At pH 3.0, the amount of calcium and phosphorus in the extract decreased at low aluminum levels and increased when more aluminum was added; however, solubilization was always inferior to that observed in the matrix solution (without aluminum). At pH 4.0, the aluminum effect on the rock solubilization was constant and negative, regardless of levels.